Isolating membrane, electrochemical device comprising isolating membrane and electric device

By applying a specific proportion of organic coatings with carbon and fluorine distribution on the isolation film of the lithium-ion battery, the performance degradation of lithium-ion batteries under high current and low temperature conditions is solved, and higher fast charging performance and low temperature stability are achieved.

CN119674455APending Publication Date: 2025-03-21NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411844527.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Lithium-ion batteries swell under high current conditions, resulting in a decrease in the migration rate of lithium-ion and a decrease in effective discharge capacity under low temperature conditions, limiting the maximum charging rate and application performance of lithium-ion batteries.

Method used

A barrier film is provided, which includes a base film and an organic coating on at least one surface of the base film, and a specific proportion of carbon and fluorine elements are distributed so that the polymer and fluorine-containing substances are uniformly distributed, the surface active site of the positive electrode material is maintained, the lithium ion migration rate is avoided to reduce the lithium ion migration rate under high current conditions, and the carbonate solvent in the electrolyte is replaced at low temperatures to reduce side reactions and interface gas production.

Benefits of technology

The fast charging performance and low-temperature intermittent circulation performance of electrochemical devices are improved, and the maximum charging rate of lithium-ion batteries and the stability at low temperatures are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189095200000171
    Figure BDA0005189095200000171
  • Figure BDA0005189095200000172
    Figure BDA0005189095200000172
  • Figure BDA0005189095200000181
    Figure BDA0005189095200000181
Patent Text Reader

Abstract

The invention provides an isolating membrane which comprises a base membrane and an organic coating arranged on at least one surface of the base membrane, in a 10 [mu] m * 5 [mu] m area of the organic coating, based on the mass of the organic coating, the mass percentage content of carbon in the organic coating is W1, the mass percentage content of fluorine in the organic coating is W2, and W1 / W2 is larger than or equal to 0.45 and smaller than or equal to 6. By adopting the isolating membrane provided by the invention, the reduction of the migration rate of lithium ions caused by swelling and hole blocking of excessive fluorine-containing substances and polymers in electrolyte can be avoided under the condition of high current, so that the fast charging performance of the lithium ion battery can be improved. And at low temperature, the electrochemical reaction rate can be reduced, and part of fluorine-containing substances can replace a carbonate solvent in the electrolyte to enter the electrolyte, so that the low-temperature intermittent cycle performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application with application number 202411418538.4, application date October 11, 2024, and invention name “An isolation membrane, an electrochemical device comprising the isolation membrane, and an electrical device”. Technical Field

[0002] The present application relates to the field of electrochemical technology, and in particular to an isolation membrane, an electrochemical device comprising the isolation membrane, and an electrical device. Background Art

[0003] Lithium-ion batteries have the characteristics of high specific energy, high operating voltage, low self-discharge rate, small size and light weight. As people's demand for diversified application scenarios of lithium-ion batteries increases, lithium-ion batteries are also more widely used in portable electronic devices, drones, electric cleaning tools, electronic cars, electric vehicles, and household energy storage equipment.

[0004] With the rapid development of lithium-ion battery applications in electric vehicles and other fields, users' demand for shortening the charging time of lithium-ion batteries has become increasingly prominent, and the disadvantage that its low-temperature performance is difficult to adapt to low-temperature environments has become increasingly obvious. Under high current conditions, the lithium-ion battery separator will swell, resulting in a decrease in the migration rate of lithium ions, which restricts the maximum charging rate of lithium-ion batteries; under low temperature conditions, the performance of lithium-ion batteries, such as effective discharge capacity, will drop significantly, restricting the application of lithium-ion batteries. Therefore, the fast charging performance and low-temperature performance of lithium-ion batteries need to be improved urgently. Summary of the invention

[0005] The purpose of the present application is to provide an isolation membrane, an electrochemical device comprising the isolation membrane, and an electrical device, so as to improve the fast charging performance of the electrochemical device and enhance the low-temperature intermittent cycle performance of the electrochemical device.

[0006] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:

[0007] The first aspect of the present application provides an isolation membrane, which includes a base membrane and an organic coating disposed on at least one surface of the base membrane. In the 10μm×5μm area of ​​the organic coating, based on the mass of the organic coating, the mass percentage of carbon element in the organic coating is W1, the mass percentage of fluorine element in the organic coating is W2, 0.45≤W1 / W2≤6, preferably, 0.45≤W1 / W2≤4.5, and more preferably, 0.45≤W1 / W2≤3. When the mass ratio of carbon element to fluorine element in the organic coating W1 / W2 is within the scope of the present application, the polymer and fluorine-containing substance on the isolation membrane are evenly distributed, so that the surface active sites on the corresponding positive electrode material are maintained, avoiding the reduction of lithium ion migration rate after excessive fluorine-containing substances and polymers swell and block pores in the electrolyte under high current conditions, thereby improving the fast charging performance of the electrochemical device. At low temperatures, the electrochemical reaction rate will decrease. Some fluorine-containing substances can replace the carbonate solvent in the electrolyte and enter the electrolyte, thereby reducing the occurrence of side reactions, improving the gas production at the interface, and improving the low-temperature intermittent cycling performance of the electrochemical device.

[0008] In one embodiment of the present application, the organic coating includes a first polymer and a second polymer, the first polymer includes at least one of a homopolymer and a copolymer of at least one monomer of propylene, vinylidene fluoride, acrylic acid, acrylate, styrene, acrylonitrile, maleic anhydride, vinyl chloride or allyl chloride; the second polymer includes at least one of a homopolymer and a copolymer of at least one monomer of vinylidene fluoride or hexafluoropropylene. Based on the mass of the organic coating, the mass percentage of the first polymer is W3, 35%≤W3≤75%; the mass percentage of the second polymer is W4, 20%≤W4≤60%. By selecting the above-mentioned first polymer and the second polymer, and regulating the values ​​of W3 and W4 within the above-mentioned range, it is beneficial to meet the range of W1 / W2, thereby improving the fast charging performance and low-temperature intermittent cycle performance of the electrochemical device.

[0009] In one embodiment of the present application, the thickness of the organic coating is d1, the thickness of the isolation membrane is d2, 0.1≤d1 / d2≤0.25, 1μm≤d1≤4μm. When the ratio of the isolation membrane coating thickness to the isolation membrane thickness d1 / d2 is within the above range, the ratio of the coating thickness to the isolation membrane thickness is within a suitable range, which is more conducive to improving the fast charging performance and low-temperature intermittent cycle performance of the electrochemical device.

[0010] In one embodiment of the present application, the maximum pore size of the base membrane is r1, the average pore size is r2, the minimum pore size is r3, 0.03μm≤r1-r2≤0.14μm, and / or, 0.010μm≤r2-r3≤0.035μm. The isolation membrane that meets the above conditions has a more suitable pore structure, thereby improving the wettability of the electrolyte to the isolation membrane. By controlling r1-r2 and r2-r3 to be within the scope of the present application, the overall size of the pores on the isolation membrane is uniform, and the overall stability of the electrochemical device is improved, which is conducive to improving the problem of relatively violent electrochemical reactions caused by excessive electrolyte flow in local areas, resulting in uneven temperature rise on the surface of the electrochemical device, thereby further improving the overcharge test pass rate of the electrochemical device and improving the fast charging performance of the electrochemical device.

[0011] In one embodiment of the present application, 0.06 μm ≤ r1 ≤ 0.22 μm. When the maximum pore size of the separator meets the above range, the overall size of the holes on the separator is more uniform. When the maximum pore size of the separator meets the above range, the overall size of the holes on the separator is more uniform, the separator is not easy to break during the overcharge test, and the risk of short circuit caused by the positive electrode contacting the negative electrode active material is reduced, thereby increasing the overcharge test pass rate. In addition, lithium ions have a suitable transmission rate, and the electrolyte has good wettability to the separator.

[0012] In one embodiment of the present application, the base film includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, the polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. The obtained isolation film has a good effect on preventing short circuits and can improve the safety performance of electrochemical devices through the shutdown effect.

[0013] In one embodiment of the present application, the isolation membrane also includes an inorganic coating, and the thickness of the inorganic coating of the isolation membrane is d3, 0.01≤r1 / d3≤0.21, preferably, 0.02≤r1 / d3≤0.14. When the ratio of the inorganic coating of the isolation membrane to the maximum pore size r1 / d3 is within the above range, the isolation membrane has good strength and suitable porosity. When the electrochemical device is squeezed by external force or under high temperature conditions, the high-temperature cycle performance will not be reduced due to the easy occurrence of closed pores in the isolation membrane. Moreover, the isolation membrane has good structural stability and is not easy to affect the structural stability of the positive and negative electrodes, so that the electron transport on the surface of the positive electrode material layer and the negative electrode material layer and the lithium ion transport shuttling between the positive and negative electrodes are not easily affected, which is beneficial to improve the overcharge test pass rate of the electrochemical device.

[0014] In one embodiment of the present application, the inorganic coating includes at least one of boehmite, aluminum oxide, silicon dioxide, zirconium oxide, titanium dioxide, magnesium oxide, mullite, silicon carbide, silicon nitride, boron nitride or aluminum nitride. The inorganic coating also includes a binder, and the binder is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. The inorganic coating on the surface of the isolation membrane can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the isolation membrane, and enhance the adhesion between the isolation membrane and the positive electrode sheet and the negative electrode sheet.

[0015] The second aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator in any of the above embodiments. The electrochemical device provided by the present application has good fast charging performance and low temperature cycle intermittent cycle performance.

[0016] In one embodiment of the present application, the electrolyte includes additives, and the additives include nitrile additives and fluorine additives; the nitrile additives include at least one of ethylene glycol diethyl cyanide, adiponitrile or succinonitrile, and the fluorine additives include at least one of fluoroethylene carbonate, bisfluoroethylene carbonate, trifluoropropylene carbonate, lithium bistrifluoromethylsulfonyl imide or lithium bisfluorosulfonyl imide. Through the combined action of fluorine additives and nitrile additives, a more stable electrolyte system can be provided, thereby reducing the oxidative decomposition heat release of general carbonate solvents, reducing the temperature rise of the electrochemical device, and improving the high-temperature storage volume expansion rate of the electrochemical device by better capturing the interface gas. Thus, the above-mentioned electrolyte cooperates with the isolation membrane provided in the present application, and the fast charging performance, low-temperature intermittent cycle performance and high-temperature storage volume expansion rate of the electrochemical device are improved.

[0017] In one embodiment of the present application, based on the total mass of the electrolyte, the mass percentage of the nitrile additive is W5, the mass percentage of the fluorine additive is W6, 1%≤W5+W6≤8%, 0.3%≤W5≤6%. Introducing the above-mentioned additives into the electrolyte and regulating W5+W6 and W5 within the above-mentioned range can better suppress the temperature rise of the electrochemical device without affecting the role of the electrolyte as a lithium ion transmission medium, and the interface film formed by the nitrile additive and the fluorine additive at high temperature has the function of capturing HF gas molecules on the interface, thereby improving the storage volume expansion rate of the electrochemical device at high temperature. Thus, the above-mentioned electrolyte cooperates with the isolation membrane provided in the present application, and the fast charging performance, low-temperature intermittent cycle performance and high-temperature storage volume expansion rate of the electrochemical device are improved.

[0018] In one embodiment of the present application, the electrolyte includes acetonitrile, and the mass percentage of the acetonitrile is W7, 45%≤W7-W5≤60% based on the total mass of the electrolyte. The above additives are introduced into the electrolyte and W7-W5 is regulated within the above range. The coexistence of acetonitrile and the above nitrile additives can improve the transmission rate of active ions such as lithium ions in the electrochemical device, and promote the preferential oxidation and decomposition of other nitrile additives at the interface between the electrolyte and the positive electrode to form a solid electrolyte interface film with stable structure and performance. In addition, since acetonitrile has the characteristics of rapid ion conduction, the interface impedance under high current density is improved, thereby improving the temperature rise of the electrochemical device under high current, and reducing the gas generation at the interface of the electrochemical device at high temperature, and further improving the high-temperature storage expansion rate of the electrochemical device.

[0019] A third aspect of the present application provides an electrical device, which includes the electrochemical device in any of the aforementioned embodiments.

[0020] Beneficial effects of this application:

[0021] The present application provides an isolation membrane, which includes a base membrane and an organic coating disposed on at least one surface of the base membrane. Based on the mass of the organic coating, the mass percentage of carbon element in the organic coating is W1, and the mass percentage of fluorine element in the organic coating is W2, and 0.45≤W1 / W2≤6. When the mass ratio of carbon element to fluorine element in the organic coating W1 / W2 is within the scope of the present application, the polymer and fluorine-containing substance on the isolation membrane are evenly distributed, so that the surface active sites on the corresponding positive electrode material are maintained, avoiding excessive fluorine-containing substances and polymers swelling and plugging in the electrolyte under high current conditions, which leads to a decrease in the migration rate of lithium ions, thereby improving the fast charging performance of the electrochemical device. At low temperatures, the electrochemical reaction rate will decrease, and some fluorine-containing substances can replace carbonate solvents in the electrolyte, reduce the production of side reactions, improve the gas generation phenomenon at the interface, and improve the low-temperature intermittent cycle performance of the electrochemical device.

[0022] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0024] The present application provides an isolation film, which includes a base film and an organic coating disposed on at least one surface of the base film. In the 10μm×5μm area of ​​the organic coating, based on the mass of the organic coating, the mass percentage of carbon element in the organic coating is W1, the mass percentage of fluorine element in the organic coating is W2, 0.45≤W1 / W2≤6, preferably, 0.45≤W1 / W2≤4.5, and more preferably, 0.45≤W1 / W2≤3. For example, the mass ratio of carbon element to fluorine element W1 / W2 in the organic coating can be 0.45, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6 or a range consisting of any two of the values. The above-mentioned "organic coating disposed on at least one surface of the base film" means that the organic coating can be disposed on one surface of the base film along the thickness direction of itself, or on two surfaces of the base film along the thickness direction of itself. It should be noted that the "surface" here can be the entire area of ​​the surface of the base film, or it can be a partial area of ​​the surface of the base film. This application has no special restrictions, as long as the purpose of this application can be achieved. When the mass ratio of carbon element to fluorine element in the organic coating W1 / W2 is within the scope of this application, the polymer and fluorine-containing substance on the isolation membrane are evenly distributed, so that the surface active sites on the corresponding positive electrode material are maintained, avoiding excessive fluorine-containing substances and polymers in the electrolyte swelling and plugging pores under high current conditions, which leads to a decrease in the migration rate of lithium ions, thereby improving the fast charging performance of the electrochemical device. At low temperatures, the electrochemical reaction rate will decrease, and some fluorine-containing substances can replace carbonate solvents in the electrolyte, reduce the occurrence of side reactions, improve the gas production at the interface, and improve the low-temperature intermittent cycle performance of the electrochemical device. In this application, low temperature refers to a temperature less than or equal to 25°C.

[0025] In one embodiment of the present application, the organic coating includes a first polymer and a second polymer, the first polymer includes at least one of a homopolymer and a copolymer of at least one monomer of propylene, vinylidene fluoride, acrylic acid, acrylate, styrene, acrylonitrile, maleic anhydride, vinyl chloride or propylene chloride; the second polymer includes at least one of a homopolymer and a copolymer of at least one monomer of vinylidene fluoride or hexafluoropropylene. The organic coating also includes a dispersant and a wetting agent, the dispersant is selected from at least one of sodium carboxymethyl cellulose or potassium carboxymethyl cellulose; the wetting agent is selected from at least one of dimethyl siloxane, polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, polyoxyethylene polyoxypropylene block copolymer or polyether modified trimethyl siloxane. Based on the mass of the organic coating, the mass percentage of the first polymer is W3, 35%≤W3≤75%; the mass percentage of the second polymer is W4, 20%≤W4≤60%. For example, the mass percentage content W3 of the first polymer can be 35%, 40%, 45%, 50%, 55%, 57%, 59%, 61%, 63%, 65%, 67%, 69%, 71%, 73%, 75% or a range consisting of any two of the values; the mass percentage content W4 of the second polymer can be 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 45%, 50%, 55%, 60% or a range consisting of any two of the values. By selecting the above-mentioned first polymer and the second polymer, and regulating the values ​​of W3 and W4 within the above-mentioned range, it is beneficial to meet the range of W1 / W2, thereby improving the fast charging performance and low-temperature intermittent cycle performance of the electrochemical device.

[0026] In one embodiment of the present application, based on the mass of the organic coating, the mass percentage of the dispersant is 1% to 5%, and the mass percentage of the wetting agent is 1% to 5%.

[0027] In one embodiment of the present application, the thickness of the organic coating is d1, the thickness of the isolation film is d2, 0.1≤d1 / d2≤0.25, 1μm≤d1≤4μm. For example, the ratio of the thickness of the coating on the isolation film to the thickness of the isolation film d1 / d2 can be 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25 or a range consisting of any two of them; the thickness of the organic coating d1 can be 1μm, 2μm, 3μm, 4μm or a range consisting of any two of them. When the thickness ratio increases, the migration of lithium ions becomes more tortuous and complex, which will affect the rate of lithium ion migration; when the thickness ratio decreases, the thickness of the coating decreases and the thickness of the substrate increases, which will affect the overall structural stability and mechanical strength of the separator, and the probability of closed pores in the separator increases, thereby affecting the fast charging performance and low-temperature intermittent cycle performance of the electrochemical device. When the ratio of the separator coating thickness to the separator thickness d1 / d2 is within the above range, the ratio of the coating to the overall thickness of the separator is within a suitable range, which is more conducive to improving the fast charging performance and low-temperature intermittent cycle performance of the electrochemical device.

[0028] In one embodiment of the present application, 9 μm ≤ d2 ≤ 16 μm. For example, d2 may be 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, or a range consisting of any two of these values.

[0029] In one embodiment of the present application, the maximum pore size of the base membrane is r1, the average pore size is r2, the minimum pore size is r3, 0.03μm≤r1-r2≤0.14μm, and / or, 0.010μm≤r2-r3≤0.035μm. For example, the difference r1-r2 between the maximum pore size and the average pore size of the base membrane can be 0.03μm, 0.05μm, 0.07μm, 0.09μm, 0.11μm, 0.13μm, 0.14μm, and / or, the difference r2-r3 between the average pore size and the minimum pore size can be 0.010μm, 0.015μm, 0.020μm, 0.025μm, 0.030μm, 0.035μm or a range consisting of any two of the values. The isolation membrane that meets the above conditions has a more suitable pore structure, thereby improving the wettability of the electrolyte to the isolation membrane. During constant current charging, when the electrochemical device is in an overcharge condition, the pores of the isolation membrane as a whole will not be too large or too many, so as to reduce the probability of overcharge caused by high-speed migration of lithium ions, thereby improving the overcharge test pass rate. When r1-r2 and r2-r3 are controlled within the scope of this application, the overall size of the pores on the isolation membrane is uniform, and the overall stability of the electrochemical device is improved, which is conducive to improving the problem of relatively violent electrochemical reactions caused by excessive electrolyte flow in local areas, resulting in uneven temperature rise on the surface of the electrochemical device, thereby further improving the overcharge test pass rate of the electrochemical device and improving the fast charging performance of the electrochemical device.

[0030] In one embodiment of the present application, 0.06μm≤r1≤0.22μm. For example, the maximum pore size r1 of the base membrane can be 0.06μm, 0.08μm, 0.10μm, 0.13μm, 0.14μm, 0.17μm, 0.20μm, 0.22μm or a range consisting of any two of these values. When the maximum pore size of the isolation membrane meets the above range, the overall size of the holes on the isolation membrane is more uniform, the isolation membrane is not easy to break during the overcharge test, and the risk of short circuit caused by the positive electrode contacting the negative electrode active material is reduced, thereby increasing the overcharge test pass rate. In addition, lithium ions have a suitable transmission rate, and the electrolyte has good wettability to the isolation membrane.

[0031] In one embodiment of the present application, 0.02 μm ≤ r2 ≤ 0.1 μm. For example, r2 may be 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, 0.1 μm, or a range consisting of any two of these values.

[0032] In one embodiment of the present application, 0.009 μm≤r3≤0.04 μm. For example, r3 may be 0.009 μm, 0.01 μm, 0.015 μm, 0.02 μm, 0.025 μm, 0.03 μm, 0.035 μm, 0.04 μm, or a range consisting of any two of these values.

[0033] In one embodiment of the present application, the base film includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, the polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In one embodiment of the present application, the base film includes polyethylene and polypropylene, and the obtained isolation film has a good effect on preventing short circuits and can improve the safety performance of electrochemical devices through the shutdown effect.

[0034] In one embodiment of the present application, the isolation membrane further comprises an inorganic coating, which is disposed between the base membrane and the organic coating, and the thickness of the inorganic coating is d3, 0.01≤r1 / d3≤0.21, preferably, 0.02≤r1 / d3≤0.14. For example, the ratio of the maximum pore size of the isolation membrane to the thickness of the inorganic coating r1 / d3 can be 0.01, 0.02, 0.05, 0.07, 0.10, 0.1, 0.14, 0.17, 0.20, 0.21 or a range consisting of any two of these values. When the ratio r1 / d3 of the inorganic coating to the maximum pore size of the isolation membrane is within the above range, the isolation membrane has good strength and suitable porosity. When the electrochemical device is squeezed by external force or under high temperature conditions, the high temperature cycle performance will not be reduced due to the easy occurrence of closed pores in the isolation membrane. Moreover, the isolation membrane has good structural stability and is not easy to affect the structural stability of the positive electrode and the negative electrode, so that the electron transmission on the surface of the positive electrode material layer and the negative electrode material layer and the lithium ion transmission shuttling between the positive electrode and the negative electrode are not easily affected, which is beneficial to improve the overcharge test pass rate of the electrochemical device.

[0035] In one embodiment of the present application, 1 μm≤d3≤4 μm. For example, d3 may be 1 μm, 2 μm, 3 μm, 4 μm, or a range consisting of any two of these values.

[0036] In the present application, isolation membranes with different r1, r2, and r3 can be purchased, and in combination with the pore size testing method provided in the present application, the isolation membrane with the required r1, r2, and r3 can be selected.

[0037] In one embodiment of the present application, the inorganic coating includes inorganic particles, and the inorganic particles include at least one of boehmite, aluminum oxide, silicon dioxide, zirconium oxide, titanium dioxide, magnesium oxide, mullite, silicon carbide, silicon nitride, boron nitride or aluminum nitride. The inorganic coating also includes a binder, and the binder is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene or polyhexafluoropropylene. The inorganic coating on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the positive electrode sheet and the negative electrode sheet.

[0038] In one embodiment of the present application, the inorganic coating comprises inorganic particles and a binder. Based on the mass of the inorganic coating, the mass percentage of the inorganic particles is 80% to 99%, and the mass percentage of the binder is 1% to 20%.

[0039] In one embodiment of the present application, the isolation film includes an inorganic coating layer, two organic coating layers and a base film, the inorganic coating layer is arranged on one side of the base film, the organic coating layer is arranged on both sides of the base film, and the inorganic coating layer is located between the organic coating layer and the base film. In one embodiment of the present application, the side of the base film on which the inorganic coating layer is arranged faces the positive electrode.

[0040] In one embodiment of the present application, the isolation film includes two inorganic coating layers, two organic coating layers and a base film, the inorganic coating layers are arranged on both sides of the base film, the organic coating layers are arranged on both sides of the base film, and the inorganic coating layers are located between the organic coating layers and the base film.

[0041] The second aspect of the present application provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator in any of the above embodiments. Thus, the electrochemical device provided by the present application has good fast charging performance and low-temperature cycle intermittent cycle performance.

[0042] In one embodiment of the present application, the electrolyte includes additives, and the additives include nitrile additives and fluorine additives; the nitrile additives include at least one of ethylene glycol diethyl cyanide, adiponitrile or succinonitrile, and the fluorine additives include at least one of fluoroethylene carbonate, bisfluoroethylene carbonate, trifluoropropylene carbonate, bistrifluoromethylsulfonyl imide lithium or bisfluorosulfonyl imide lithium. The introduction of the above additives into the electrolyte can reduce the temperature rise of the electrochemical device under high current. When the electrolyte in the electrochemical device meets the above conditions, the synergistic effect between the nitrile additives and the fluorine additives can form a solid electrolyte interface film with an endothermic effect, and the solid electrolyte interface film decomposes at the interface in priority to the general carbonate solvent, thereby reducing the heat generated during the oxidation and decomposition of the carbonate solvent and reducing the temperature rise of the electrochemical device. And the solid electrolyte interface film formed by the nitrile additives and the fluorine additives at high temperature has the effect of capturing HF gas molecules at the interface, thereby improving the storage volume expansion rate of the electrochemical device at high temperature. Through the combined action of fluorine additives and nitrile additives, a more stable electrolyte system can be provided, thereby reducing the oxidative decomposition heat release of general carbonate solvents, reducing the temperature rise of the electrochemical device, and improving the high-temperature storage volume expansion rate of the electrochemical device by better capturing the interface gas. Thus, the above-mentioned electrolyte and the isolation membrane provided by the present application cooperate with each other, and the fast charging performance, low-temperature intermittent cycle performance and high-temperature storage volume expansion rate of the electrochemical device are all improved.

[0043] In one embodiment of the present application, based on the total mass of the electrolyte, the mass percentage of the nitrile additive is W5, the mass percentage of the fluorine additive is W6, 1%≤W5+W6≤8%, 0.3%≤W5≤6%. For example, based on the total mass of the electrolyte, the sum of the contents of the nitrile additive and the fluorine additive W5+W6 can be 1%, 3%, 5%, 7%, 8% or a range consisting of any two of the values; the mass percentage of the nitrile additive W5 can be 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6% or a range consisting of any two of the values. Introducing the above additives into the electrolyte and regulating W5+W6 and W5 within the above range can better suppress the temperature rise of the electrochemical device, and does not affect the role of the electrolyte as a lithium ion transmission medium, and the interface film formed by the nitrile additive and the fluorine additive at high temperature has the function of capturing the HF gas molecules at the interface, thereby improving the storage volume expansion rate of the electrochemical device at high temperature. Thus, the above-mentioned electrolyte cooperates with the isolation membrane provided in the present application, and the fast charging performance, low-temperature intermittent cycle performance and high-temperature storage volume expansion rate of the electrochemical device are improved.

[0044] In one embodiment of the present application, 0.5%≤W6≤7%. For example, W6 can be 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, or a range consisting of any two of these values.

[0045] In one embodiment of the present application, the electrolyte includes acetonitrile, and the mass percentage of acetonitrile is W7, 45%≤W7-W5≤60% based on the total mass of the electrolyte. For example, based on the total mass of the electrolyte, the difference between the content of acetonitrile and the fluorine additive W7-W5 can be 45%, 47%, 49%, 51%, 53%, 55%, 57%, 59%, 60% or a range consisting of any two of the values. The above additives are introduced into the electrolyte and W7-W5 is regulated within the above range. The coexistence of acetonitrile and the above nitrile additives can improve the transmission rate of active ions such as lithium ions in the electrochemical device, and promote the preferential oxidation and decomposition of the nitrile additives at the interface between the electrolyte and the positive electrode to form a solid electrolyte interface film with stable structure and performance, and because acetonitrile has the characteristics of rapid ion conduction, the interface impedance at high current density is improved, thereby improving the temperature rise of the electrochemical device at high current, and reducing the gas generation at the interface of the electrochemical device at high temperature, further improving the high temperature storage expansion rate of the electrochemical device.

[0046] In one embodiment of the present application, 45.3%≤W7≤66%. For example, W7 can be 45.3%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66% or a range consisting of any two of the values.

[0047] There is no particular restriction on the positive electrode sheet in the present application, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet generally includes a positive current collector and a positive active material layer. Among them, the positive current collector is not particularly limited, and can be any positive current collector in the art, such as aluminum foil, aluminum alloy foil or composite current collector. The positive active material layer includes a positive active material, and the positive active material is not particularly limited. Any positive active material in the art can be used, for example, it can include lithium nickel cobalt manganese oxide (811, 622, 523, 111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide, lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. At least one of.

[0048] The present application has no particular limitation on the thickness of the positive electrode current collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the positive electrode material layer is 30 μm to 120 μm.

[0049] In the present application, the positive electrode material layer may also include a positive electrode conductor and a positive electrode binder. The present application does not particularly limit the types of the conductor and the binder, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers, and specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. For example, the positive electrode binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the positive electrode active material, the conductive agent, and the binder in the positive electrode material layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0050] There is no particular limitation on the negative electrode plate in the present application, as long as the purpose of the present application can be achieved. For example, the negative electrode plate generally comprises a negative electrode current collector and a negative electrode active material layer. Among them, the negative electrode current collector is not particularly limited, and any negative electrode current collector in the art can be used, such as copper foil, aluminum foil, aluminum alloy foil, and composite current collector. The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material is not particularly limited, and any negative electrode active material in the art can be used. For example, it can include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon, hard carbon, silicon, silicon carbon, lithium titanate, etc.

[0051] In the present application, the negative electrode material layer may also include a negative electrode conductive agent and a negative electrode binder. The present application has no particular restrictions on the types of the negative electrode conductive agent and the negative electrode binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the above-mentioned positive electrode conductive agent and the above-mentioned positive electrode binder. The present application has no particular restrictions on the mass ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder in the negative electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.

[0052] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode material layer is 30 μm to 120 μm. The present application has no particular limitation on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 4 μm to 15 μm.

[0053] The electrolyte of the present application further comprises a lithium salt and a non-aqueous solvent.

[0054] In some embodiments of the present application, the lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiC(SO2CF3)3, LiSiF6, LiBOB and lithium difluoroborate. The present application has no particular restrictions on the content of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the lithium salt is 8% to 15%.

[0055] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof.

[0056] The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0057] Examples of the above-mentioned linear carbonate compounds are dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) and combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate and combinations thereof.

[0058] Examples of the above carboxylic acid ester compounds are methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid lactone, valerolactone, mevalonolactone, caprolactone and combinations thereof.

[0059] Examples of the above ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.

[0060] Examples of the above other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, phosphoric acid esters and combinations thereof.

[0061] The present application has no particular limitation on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the mass of the electrolyte, the mass percentage of the non-aqueous solvent is 11% to 92%.

[0062] In one embodiment of the present application, the electrolyte includes a lithium salt and a non-aqueous solvent, the mass percentage of the lithium salt is as shown above, and the mass percentage of the non-aqueous solvent is 85% to 92%. The electrochemical device including the above electrolyte has improved fast charging performance and low-temperature intermittent cycle performance.

[0063] In one embodiment of the present application, the electrolyte includes an additive, a lithium salt and a non-aqueous solvent, the additive includes the above-mentioned nitrile additive and the above-mentioned fluorine additive, the mass percentage of the nitrile additive, the fluorine additive and the lithium salt is as shown above, and the mass percentage of the non-aqueous solvent is 77% to 91%. The electrochemical device including the above-mentioned electrolyte has improved fast charging performance, low-temperature intermittent cycle performance and high-temperature storage volume expansion rate.

[0064] In one embodiment of the present application, the electrolyte includes an additive, acetonitrile, a lithium salt, and a non-aqueous solvent, wherein the additive includes the above-mentioned nitrile additive and the above-mentioned fluorine additive, the mass percentages of the nitrile additive, the fluorine additive, the acetonitrile, and the lithium salt are as shown above, and the mass percentage of the non-aqueous solvent is 11% to 54%. The electrochemical device including the above-mentioned electrolyte has improved fast charging performance, low-temperature intermittent cycle performance, and high-temperature storage volume expansion rate.

[0065] In one implementation of the present application, taking a lithium-ion battery as an example, the positive electrode sheet, the separator, and the negative electrode sheet are wound or stacked in sequence to form an electrode assembly, which is then packaged in a shell such as an aluminum-plastic film, and an electrolyte is injected, formed, and packaged to form a lithium-ion battery.

[0066] A third aspect of the present application provides an electrical device, which includes the electrochemical device in any of the aforementioned embodiments.

[0067] The present application does not particularly limit the type of electrical device, and it can be used for any electrical device known in the prior art. In some embodiments of the present application, the electrical device may include, but is not limited to, a notebook computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0068] Example

[0069] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0070] Test methods and equipment:

[0071] Fast charging test:

[0072] Step 1: In an environment of 25°C, charge the lithium-ion battery with a constant current at a charging current of 2C until the upper voltage reaches 4.3V. Let the fully charged lithium-ion battery stand for 2 hours, then discharge it to 2.0V at a discharge current of 0.5C, and record the discharge capacity during 2C charging.

[0073] Step 2: In an environment of 25°C, charge the lithium-ion battery with a constant current at a charging current of 1 / 3C until the upper voltage reaches 4.3V. Let the fully charged lithium-ion battery stand for 2 hours, then discharge it to 2.0V at a discharge current of 0.5C, and record the discharge capacity when charging at 1 / 3C.

[0074] The lithium ion batteries prepared in the embodiment and the comparative example were respectively subjected to the operations of step 1 and step 2 in sequence, and then the rate charging capacity retention rate of the lithium ion battery was calculated using the following expression:

[0075] The charge retention rate of a lithium-ion battery at a rate of 2C = (the discharge capacity of the lithium-ion battery when charged at 2C / the discharge capacity of the lithium-ion battery when charged at 1 / 3C) × 100%.

[0076] Capacity retention test after 400 cycles at -15°C:

[0077] Step 1: In an environment of -15°C, charge the lithium-ion battery for the first time: perform constant current charging at a charging current of 0.7C until the upper limit voltage is 4.3V, then perform constant voltage charging at 4.3V until the current is 0.05C, record the thickness D0 of the fully charged lithium-ion battery, and let the fully charged lithium-ion battery stand to ensure that the constant current charging time, constant voltage charging time plus the standing time are 24h;

[0078] Step 2: In an environment of -15°C, discharge at a rate of 0.5C to 2.0V, record the discharge capacity of the first cycle, and then let it stand for 2 hours;

[0079] Step 3: In an environment of -15°C, charge the lithium-ion battery: perform constant current charging at a charging current of 0.7C until the upper limit voltage is 4.3V, then perform constant voltage charging at 4.3V until the current is 0.05C, and let the fully charged lithium-ion battery stand for 2 hours, ensuring that the constant current and constant voltage charging time plus the standing time is 24 hours;

[0080] Step 4: In an environment of -15°C, discharge at a rate of 0.5C to 2.0V, and then let it stand for 1 hour;

[0081] Step 5: Cycle the above steps 3 to 4 for 399 times, record the 399th cycle discharge capacity of the lithium-ion battery, and then calculate the low-temperature capacity retention rate of the lithium-ion battery at -15°C using the following expression:

[0082] Cycle capacity retention rate = (discharge capacity at the 400th cycle / discharge capacity at the first cycle) × 100%, recorded as “-15° C. intermittent cycle capacity retention rate”.

[0083] Gas production test:

[0084] At 25°C, constant current charging is performed at a current value of 1C until the voltage reaches 4.3V, and constant voltage charging is performed at 4.3V until the current reaches 0.05C. Then, the charged lithium-ion battery is stored in a constant temperature chamber at 25°C for 2 hours, and constant current discharge is performed at a discharge current of 0.1C until the final voltage reaches 2.0V. This is a charge and discharge cycle. Three cycles are performed to measure the gas generation of the lithium-ion battery within three cycles, and the gas generation is used to evaluate the storage characteristics of the lithium-ion battery. The gas generation can be tested using an in-situ gas generation meter, and the gas generation can be determined by testing the change in the volume of the lithium-ion battery.

[0085] Wettability test:

[0086] At 25°C, in a glove box, use a pipette with a range of 1 μL to 5 μL to fill 5 mL of the lithium battery electrolyte prepared in the examples and comparative examples, drop it on the isolation membrane respectively, and record the time required for the electrolyte to be completely absorbed by the electrode.

[0087] Overcharge test pass rate:

[0088] 3C-5V overcharge test: Under the condition of ambient temperature of 25±5℃, discharge the lithium-ion battery to 2.0V at a discharge current of 0.5C, charge the discharged lithium-ion battery to 5.0V at a constant current of 3C, and then change to 5V constant voltage charging. The constant voltage charging time is limited to 6 hours or the charging is stopped when the temperature difference of the lithium-ion battery surface temperature within 45min is ≤2℃. Judgment standard: The lithium-ion battery passes the test if it does not catch fire. 20 lithium-ion batteries are tested for each embodiment and comparative example. Overcharge test pass rate = number of passed batteries / 20×100%.

[0089] Charging temperature rise test:

[0090] Step 1: In an environment of 25°C, charge the lithium-ion battery with a constant current of 0.5C until the upper voltage reaches 4.3V, and record the surface temperature T1 of the lithium-ion battery. Then discharge it to 2.0V with a discharge current of 0.5C, and let it stand until the surface temperature of the lithium-ion battery reaches 25°C.

[0091] Step 2: Charge at a constant current of 6C until the upper limit voltage reaches 4.3V. Continue charging for 5 hours and record the surface temperature T2 of the lithium-ion battery after charging to the upper limit voltage of 4.3V.

[0092] The lithium ion batteries prepared in the embodiment and the comparative example were respectively subjected to the operations of step 1 and step 2, and then the degree of surface temperature rise of the lithium ion battery was calculated using the following expression:

[0093] The temperature rise of a lithium-ion battery when charged at 6C = the surface temperature T2 of the lithium-ion battery when the lithium-ion battery is charged at 6C - the surface temperature T1 of the lithium-ion battery when the lithium-ion battery is charged at 0.5C.

[0094] High temperature storage volume expansion test:

[0095] Place the lithium-ion battery in a 25°C constant temperature test box, charge it to 4.3V at a constant current of 1C, then charge it to a cutoff current of 0.1C at a constant voltage of 4.3V, and then discharge it to 2.0V at a constant current of 0.5C, which is recorded as the initial discharge capacity of the lithium-ion battery. Then charge it to 4.3V at a constant current of 1C, then charge it to a cutoff current of 0.1C at a constant voltage of 4.3V, take out the lithium-ion battery test volume and record it as the initial volume of the lithium-ion battery, then transfer the lithium-ion battery to 85°C and let it stand for 12 hours, take out the lithium-ion battery test volume and record it as the thickness of the lithium-ion battery after high-temperature storage, place the lithium-ion battery in a 25°C constant temperature test box, let it stand until the lithium-ion battery reaches a constant temperature of 25°C, then discharge it to 2.0V at a constant current of 0.5C, and record the discharge capacity as the discharge capacity of the lithium-ion battery after high-temperature storage. Use the following expression to calculate the high-temperature storage volume change rate:

[0096] High temperature storage volume expansion rate (volume of lithium ion battery after high temperature storage - initial volume of lithium ion battery) / initial volume of lithium ion battery × 100%.

[0097] Method for measuring the mass percentage of carbon and fluorine in organic coatings:

[0098] The SEM was used to select an area of ​​10 μm×5 μm in the organic coating for X-ray energy dispersive spectrum analysis (EDS) testing. Three locations were selected and the average value was taken to calculate the mass percentage of carbon and fluorine.

[0099] Measuring electrolyte composition:

[0100] The electrolyte was tested by gas chromatography-mass spectrometry (GC-MS) and external standard method to obtain the mass percentage of components in the electrolyte.

[0101] Aperture test:

[0102] The lithium-ion battery was disassembled to obtain an isolation membrane, and the organic coating and inorganic coating on the surface of the isolation membrane were ultrasonically cleaned with dimethyl carbonate (DMC), and the base membrane was dried. Then, the pore size distribution of the base membrane was tested with a pore size distribution tester, thereby obtaining the maximum pore size r1, the average pore size r2, and the minimum pore size r3 of the base membrane.

[0103] Example 1-1

[0104] <Preparation of positive electrode sheet>

[0105] The positive electrode active materials lithium cobalt oxide, acetylene black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 94:3:3, and then N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75%, and stirred evenly. The slurry is evenly coated on one surface of an aluminum foil with a thickness of 12μm, dried at 90°C, and cold pressed to obtain a positive electrode sheet with a positive electrode active material layer thickness of 42μm, and then the above steps are repeated on the other surface of the positive electrode sheet to obtain a positive electrode sheet with a positive electrode active material layer coated on both sides. The positive electrode sheet is cut into a specification of 74mm×867mm and welded to the pole ear for standby use.

[0106] <Preparation of negative electrode sheet>

[0107] The negative electrode active material artificial graphite, acetylene black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 96:1:1.5:1.5, and then deionized water is added as a solvent to prepare a slurry with a solid content of 70%, and stirred evenly. The slurry is evenly coated on one surface of a copper foil with a thickness of 8 μm, dried at 110°C, and cold pressed to obtain a negative electrode sheet with a single-sided negative electrode active material layer coated with a negative electrode active material layer with a thickness of 54.5 μm, and then the above coating steps are repeated on the other surface of the negative electrode sheet to obtain a negative electrode sheet with a double-sided negative electrode active material layer coated. The negative electrode sheet is cut into a specification of 74 mm × 867 mm and welded to the pole ear for standby use.

[0108] <Preparation of Electrolyte>

[0109] In an environment with a water content of less than 10ppm, non-aqueous organic solvents of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 2:5:3, and then lithium hexafluorophosphate (LiPF6) is added to the non-aqueous organic solvent to dissolve and mix evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of LiPF6 is 9%.

[0110] <Preparation of Separator Film>

[0111] Preparation of inorganic coating:

[0112] Boehmite with a volume average particle size Dv50 of 1 μm and a binder polyacrylate were added to a stirrer at a mass ratio of 85:15, stirred and mixed evenly, and then deionized water was added for stirring, with a solid content of 48% to obtain slurry B. The above slurry B was uniformly coated on one surface of the base film by gravure roller coating at a speed of 0.6 m / min, and dried by blowing hot air at 120°C at a wind speed of 0.5 m / sec. A 6 μm thick polyethylene (PE) microporous membrane was selected as the base membrane, and the inorganic coating thickness d3 was 3 μm.

[0113] Organic coating preparation:

[0114] The mass ratio of the first polymer, the second polymer, sodium carboxymethyl cellulose, and dimethyl siloxane is 50:45:0.7:4.3. Polypropylene with a melt index of 8g / 10min is used as the first polymer, and polyvinylidene fluoride with a melt index of 1g / 10min is used as the second polymer. The first polymer and the second polymer are added to the stirrer and stirred to mix evenly. Sodium carboxymethyl cellulose is added to the stirrer and stirred evenly; dimethyl siloxane, a wetting agent, is added to the stirrer, and then deionized water is added for stirring, and the slurry viscosity is adjusted to 38mPa·s and the solid content is 5% to obtain slurry A; slurry A is evenly applied on the surface of the inorganic coating, dried in an oven, and then slurry A is applied to the other surface of the base film, and dried to obtain an isolation film. The thickness d1 of the organic coating is 2μm, and the thickness d2 of the isolation film is 13μm.

[0115] <Preparation of lithium-ion batteries>

[0116] The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, and the side of the separator provided with the inorganic coating faces the positive electrode sheet, and the electrode assembly is wound. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the water is removed at 80°C, and the prepared electrolyte is injected. The lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping, and other processes. Among them, the upper limit voltage of the formation is 4.15V, the formation temperature is 70°C, and the formation standing time is 2h.

[0117] Example 1-2

[0118] Except that in <Preparation of organic coating>, the first polymer is changed to polyvinylidene fluoride (melt index is 8 g / 10 min), the second polymer is changed to polyhexafluoropropylene (melt index is 1 g / 10 min), and the relevant preparation parameters are adjusted according to Table 1, the rest is the same as Example 1-1.

[0119] Example 1-3 to Example 1-14

[0120] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.

[0121] Example 2-1 to Example 2-16

[0122] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1-1.

[0123] Example 3-1

[0124] The preparation of the electrolyte is the same as Example 1-1 except that nitrile additives and fluorine additives are added according to Table 3. When the sum of the contents of nitrile additives and fluorine additives W5+W6 changes, the content of the organic solvent changes accordingly, and the mass percentage of LiPF6 remains unchanged.

[0125] <Preparation of Electrolyte>

[0126] In an environment with a water content of less than 10ppm, non-aqueous organic solvents ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 2:5:3 to obtain a base solvent. Ethylene glycol diethyl cyanide, fluoroethylene carbonate, and lithium hexafluorophosphate (LiPF6) are added to the base solvent and stirred evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of LiPF6 is 9%; the mass percentage of ethylene glycol diethyl cyanide is 2%; and the mass percentage of fluoroethylene carbonate is 2%.

[0127] Example 3-2 to Example 3-8

[0128] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 3-1.

[0129] Embodiment 3-9

[0130] Except for the addition of acetonitrile in the preparation of electrolyte, the rest is the same as Example 3-1. When the mass percentage content W7 of acetonitrile changes, the content of organic solvent changes accordingly, and the mass percentage content of LiPF6 remains unchanged.

[0131] <Preparation of Electrolyte>

[0132] In an environment where the water content is less than 10ppm, non-aqueous organic solvents ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 2:5:3 to obtain a base solvent. Ethylene glycol diacetonitrile ether, fluoroethylene carbonate, acetonitrile and lithium hexafluorophosphate (LiPF6) are added to the base solvent and stirred evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of LiPF6 is 9%; the mass percentage of ethylene glycol diacetonitrile ether is 2%; the mass percentage of fluoroethylene carbonate is 2%; and the mass percentage of acetonitrile is 55%.

[0133] Example 3-10 and Example 3-15

[0134] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 3-9. When the sum of the contents of nitrile additives and fluorine additives W5+W6 and the mass percentage of acetonitrile W7 change, the content of the organic solvent changes accordingly, and the mass percentage of LiPF6 remains unchanged.

[0135] Comparative Example 1 and Comparative Example 2

[0136] Except for adjusting W1 / W2 according to Table 1, the rest is the same as Example 1-1.

[0137] The preparation parameters and test results of each embodiment and comparative example are shown in Tables 1 to 3 below:

[0138] Table 1

[0139]

[0140] It can be seen from Examples 1-1 to 1-7, Comparative Examples 1 and 2 in Table 1 that when the mass ratio of carbon element to fluorine element W1 / W2 in the isolation membrane coating is within the range of the present application, the obtained lithium-ion battery has a higher 2C rate charge retention rate and -15°C intermittent cycle capacity retention rate, indicating that the fast charging performance and low-temperature intermittent cycle performance of the lithium-ion battery are improved.

[0141] The ratio of the thickness of the isolation film coating to the thickness of the isolation film d1 / d2 and the thickness of the organic coating d1 usually affect the overall structural stability of the isolation film, and thus affect the fast charging performance and low-temperature intermittent cycle performance of the lithium-ion battery. It can be seen from Examples 1-1, 1-8 to 1-14 that when the ratio of the thickness of the isolation film coating to the thickness of the isolation film d1 / d2 and the thickness of the organic coating d1 are within the range of the present application, the obtained lithium-ion battery has a higher 2C rate charge retention rate and -15°C intermittent cycle retention rate, indicating that the fast charging performance and low-temperature intermittent cycle performance of the lithium-ion battery are improved.

[0142] Table 2

[0143]

[0144]

[0145] It can be seen from Examples 1-1 and 2-1 to 2-16 that when the difference r1-r2 between the maximum pore size and the average pore size, r2-r3 between the average pore size and the minimum pore size, and the maximum pore size r1 of the base membrane are within the scope of the present application, the obtained lithium-ion battery has a shorter wetting time and a higher overcharge test pass rate, indicating that the wettability of the isolation membrane is improved and the overcharge phenomenon of the lithium-ion battery is reduced.

[0146] The ratio r1 / d3 of the first coating layer of the isolation membrane to the maximum pore size usually affects the structural stability of the isolation membrane material, thereby affecting the structural stability of the positive electrode, resulting in the influence of the electron transmission on the surface of the active material and the lithium ion transmission shuttling between the positive and negative electrodes, and finally affecting the overcharge test pass rate of the electrochemical device. It can be seen from Examples 1-1, 2-1 to 2-16 that when the ratio r1 / d3 of the first coating layer of the isolation membrane to the maximum pore size is within the scope of this application, the obtained lithium-ion battery has a shorter immersion time and a higher overcharge test pass rate, indicating that the wettability of the isolation membrane is improved and the overcharge phenomenon of the lithium-ion battery is reduced.

[0147] Table 3

[0148]

[0149]

[0150] Note: “ / ” in Table 3 indicates that there are no relevant preparation parameters.

[0151] It can be seen from Example 1-1, Example 3-1 and Example 3-5 to Example 3-8, and Example 3-12 to Example 3-13 that when the sum of the contents of nitrile additives and fluorine additives W5+W6 and the mass percentage content of nitrile additives W5 are within the scope of this application, the obtained lithium ion battery has a smaller 6C charging temperature rise and high-temperature storage volume expansion rate, indicating that the electrochemical performance of the lithium ion battery at high temperature and high current density is improved.

[0152] It can be seen from Example 1-1, Example 3-1 to Example 3-4 that when the types of nitrile additives and fluorine additives are within the scope of the present application, the obtained lithium ion battery has good 6C charging temperature rise and high temperature storage volume expansion rate, indicating that the electrochemical performance of the lithium ion battery at high temperature and high current density is improved.

[0153] It can be seen from Examples 3-1 and 3-9 to 3-15 that acetonitrile has good superposition with nitrile additives, fluorine additives and propylene carbonate. When the difference between the mass percentage of acetonitrile in the electrolyte and the mass percentage of nitrile additives is W7-W5 within the scope of the present application, the obtained lithium ion battery has good 6C charging temperature rise and high temperature storage volume expansion rate, indicating that the electrochemical performance of the lithium ion battery at high temperature and high current density is improved.

[0154] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0155] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A separator, comprising a base film and an organic coating disposed on at least one surface of the base film, wherein in a region of 10 μm×5 μm of the organic coating, based on the mass of the organic coating, the mass percentage of carbon in the organic coating is W1, the mass percentage of fluorine in the organic coating is W2, and 0.45≤W1 / W2≤6; The isolation membrane also includes an inorganic coating, which is arranged between the base membrane and the organic coating. The thickness of the organic coating is d1, the thickness of the isolation membrane is d2, the thickness of the inorganic coating is d3, and the maximum pore size of the base membrane is r1, 0.1≤d1 / d2≤0.25, 0.02≤r1 / d3≤0.

21.

2. The isolation film according to claim 1, wherein: 0.45≤W1 / W2≤4.

5.

3. The isolation film according to claim 1, wherein: 0.45≤W1 / W2≤3.

4. The isolation film according to claim 1, wherein: The organic coating includes a first polymer and a second polymer, the first polymer includes at least one of a homopolymer and a copolymer of at least one monomer selected from propylene, vinylidene fluoride, acrylic acid, acrylate, styrene, acrylonitrile, maleic anhydride, vinyl chloride or allyl chloride; the second polymer includes at least one of a homopolymer and a copolymer of at least one monomer selected from vinylidene fluoride or hexafluoropropylene; based on the mass of the organic coating, the mass percentage of the first polymer is W3, 35%≤W3≤75%, and the mass percentage of the second polymer is W4, 20%≤W4≤60%.

5. The isolation film according to claim 1, wherein: 1μm≤d1≤4μm.

6. The isolation film according to claim 1, wherein: The base film includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid, and the average pore size of the base film is r2, the minimum pore size is r3, 0.03μm≤r1-r2≤0.14μm, and / or, 0.010μm≤r2-r3≤0.035μm.

7. The isolation film according to claim 6, wherein: 0.06μm≤r1≤0.22μm.

8. The isolation film according to claim 1, wherein: 0.02≤r1 / d3≤0.14。 9 . An electrochemical device comprising a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator according to claim 1 .

10. The electrochemical device according to claim 9, wherein the electrolyte comprises additives, the additives comprising nitrile additives and fluorine additives; the nitrile additives comprise at least one of ethylene glycol diethyl cyanide, adiponitrile or succinonitrile, and the fluorine additives comprise at least one of fluoroethylene carbonate, bisfluoroethylene carbonate, trifluoropropylene carbonate, lithium bistrifluoromethylsulfonyl imide or lithium bisfluorosulfonyl imide.

11. The electrochemical device according to claim 10, wherein: Based on the total mass of the electrolyte, the mass percentage of the nitrile additive is W5, the mass percentage of the fluorine additive is W6, 1%≤W5+W6≤8%, 0.3%≤W5≤6%.

12. The electrochemical device according to claim 10, wherein: The electrolyte includes acetonitrile, and based on the total mass of the electrolyte, the mass percentage of the acetonitrile is W7, 45%≤W7-W5≤60%.

13. An electrical device comprising the electrochemical device according to any one of claims 9 to 12.